Analyze Instrument for Improved Visualization Creativity In Learning Physics With Matlab Software Using PjBL and KWL - Mihardi, Satria; Bunawan, Wawan; ., Sahyar (Advances in Social Sciences Research Journal, 2017)
The purpose of this research is intended to improve the creativity of students in the products with a visualization of the equations of physics in learning by using project-based learning model and getting standardized assessment instrument in the assessment of student creativity that is specific to each indicator creativity. Model of project-based learning is an instructional model that can enhance the creativity of students through activities in learning syntax. To achieve an increase in creativity, then, the lesson is designed to be able to attract students thinking skills to a high level. Learning that can improve creativity one of which is learning by PjBL Model. By using the PjBL model students in learning activities that match the syntax. The PPA will be able to increase creativity. In addition, the use of KWL then planning the achievement of a product as a result of creativity will be more focused and systematic. So that the achievement of a product which is expected to be more effective and efficient. Research conducted at the FMIPA Unimed. The type of research conducted an action research aimed to see an increase in student creativity. To see an increase in the use of data analysis to test N-Gain. In the implementation of the research conducted in the cycle consists of four actions in one cycle.